Gestão de recursos humanos e resultados em saúde: um estudo da Atenção Primária à saúde brasileira entre 2012 - 2014 - Thiago Augusto Hernandes Rocha (2019)
Introduction: This work aims to articulate the human resources management (HRM), results of the family health strategy, against the context of primary health care (PHC), in order to evaluate the possibilities of intervention with them, to ensure a more effective health service delivery system. In effect, this discussion sheds light on the dimensions of HRM, Primary Health Care (PHC) and measurement of results, in order to address a debate necessary for the promotion of improvements in the structured health system in the country. Aspects associated with HRM have been configured as difficult to manage to ensure the materialization of the pillars recommended by PHC. The emphasis on the need to discuss aspects of HRM in health began to raise awareness among managers and formulators of public health policies, for the fact that the key to obtaining high standards of quality of health services was human. Objective of the study: The objective of this study is to describe and analyze the possible association between HRM management and the adoption of the Family Health Strategy (FHS) in Brazil between 2012 and 2014. Methodology: Regarding the design of the present study, we opted for adoption of three classifiers: research strategy, time horizon and method of data collection. In relation to the first, the present study is classified as descriptive-explanatory. As for the time horizon, the present study is configured as being from a longitudinal perspective. Finally, the method of data collection was based on secondary data. Data from four sources were analyzed: Access and Quality Improvement Program - AB, stratification of Brazilian municipalities for management purposes, ambulatory care sensitive hospitalizations (ACSH) and the population contingent with the 2010 census. The basic health units (BHU) were the analysis units totaling 37,973 units considered. The categories of analysis were: PHC guiding principles, HRM practices and results interface between HRM and PHC. A multilevel approach was used to estimate the impact of HRM actions on PHC outcomes. Results: Based on the analyzes, it was possible to identify the magnitude of impact of the structure and process elements on the volume of ACSH s, assigned to a BHU. These elements pervade the PHC guiding principles. The number of links of the medical professionals, the presence of physical facilities, equipment and desirable inputs, the availability of recommended immunobiological agents and the association with the cluster of number of HRMs were considered significant to estimate the rate of ACSH adjusted for population, two. In addition, the social determinants of health, materialized through the classification strata of the municipalities, were also determinant to estimate the volume of ACSH linked to a specific BHU. Conclusions: It was possible to identify a statistically significant association between the structural elements, both physical and human, for the volume of ACSH s by BHU. In addition, social determinants of health played an important role in the estimation of ACSH rates among the population assisted by PHC. Unexpectedly, health work process measures were not associated with ACSH in the present study. Based on the findings highlighted in the previous section, it was possible to estimate that HRM practices were associated with the chosen outcome measure.